2011
DOI: 10.1038/ismej.2011.106
|View full text |Cite
|
Sign up to set email alerts
|

Novel lineages of Prochlorococcus and Synechococcus in the global oceans

Abstract: Picocyanobacteria represented by Prochlorococcus and Synechococcus have an important role in oceanic carbon fixation and nutrient cycling. In this study, we compared the community composition of picocyanobacteria from diverse marine ecosystems ranging from estuary to open oceans, tropical to polar oceans and surface to deep water, based on the sequences of 16S-23S rRNA internal transcribed spacer (ITS). A total of 1339 ITS sequences recovered from 20 samples unveiled diverse and several previously unknown clad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
264
4
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(298 citation statements)
references
References 52 publications
28
264
4
2
Order By: Relevance
“…Their growth physiology is consistent with the environmental distribution of these clades reported in the previous studies (Zwirglmaier et al, 2007(Zwirglmaier et al, , 2008Ahlgren and Rocap, 2012;Huang et al, 2012;Sohm et al, 2016). Growth rates were marginally lower at low temperature in strains of clade I (CC9311) and IV (BL107, CC9902), which are dominant in temperate regions.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Their growth physiology is consistent with the environmental distribution of these clades reported in the previous studies (Zwirglmaier et al, 2007(Zwirglmaier et al, , 2008Ahlgren and Rocap, 2012;Huang et al, 2012;Sohm et al, 2016). Growth rates were marginally lower at low temperature in strains of clade I (CC9311) and IV (BL107, CC9902), which are dominant in temperate regions.…”
Section: Discussionsupporting
confidence: 75%
“…Clades I and IV are predominant in oceanic latitudes above 30°N and below 30°S. Clades II and III are found mostly within tropical and sub-tropical oceanic latitudes (Zwirglmaier et al, 2007(Zwirglmaier et al, , 2008Scanlan et al, 2009;Mella-Flores et al, 2011;Post et al, 2011;Ahlgren and Rocap, 2012;Mazard et al, 2012;Huang et al, 2012;Sohm et al, 2016). In relation to temperature, clades I and IV occur at higher abundances at 10 -20°C whereas clades II and III occur in the range of 20-28°C (Zwirglmaier et al, 2008) suggesting that temperature, among other environmental factors, may have a key role in their partitioning.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…For clarity and conformity with existing nomenclature, we refer to these clades as HL III and HL IV following Huang et al (2012).…”
Section: Resultsmentioning
confidence: 99%
“…Analyses of environmental DNA sequences have recently revealed new clades of HL-adapted Prochlorococcus that currently lack cultured representatives (Rusch et al, 2010;West et al, 2011;Huang et al, 2012). More specifically, Rusch et al (2010) identified two groups through phylogenetic analysis of several 'core' functional genes, that is, those common to all sequenced Prochlorococcus genomes, from the Global Ocean Survey (GOS) metagenomic data set, whereas West et al (2011) recovered novel 16S rRNA sequences in a separate sampling expedition.…”
Section: Introductionmentioning
confidence: 99%